Dentists' level of knowledge of the treatment plans for periodontal ligament injuries after dentoalveolar trauma - Pedrini, Denise [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP]; Marcal Mazza Sundefeld, Maria Lucia [UNESP]; Ferreira Tiveron, Adelisa Rodolfo [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2011)
This study investigated the level of knowledge held by dentists about the possible treatment plan procedures for periodontal ligament injuries after dentoalveolar trauma. A 5-item self-applied questionnaire was prepared with questions referring to the professional profile of the interviewees and to the treatment plan they would propose for periodontal ligament injuries secondary to dentoalveolar trauma. The questionnaires were filled out by 693 dentists attending the 23rd Annual Meeting of the Brazilian Society for Dental Research, and the data obtained were subjected to descriptive analysis. Either the chi-square test or Fisher's exact test was applied to assess associations among variables, at a 5% level of significance. The results revealed that dentists experienced difficulty in establishing a treatment plan for subluxation, and for extrusive, lateral and intrusive luxations. In general, holding a dental specialty degree had no influence on the knowledge about treatment plan procedures for the most severe injuries. It could be concluded that the dentists participating in this study, whether specialists or not, did not have sufficient knowledge to treat most of the periodontal ligament injuries resulting from dentoalveolar trauma adequately.
Keywords: Tooth Injuries; Patient Care Planning; Periodontal Ligament